Constrained optimization of s-CO2 compression train system through 1D approach under a new gas-like behavior constraint - Gasparin, Elóy [UNESP]; Mattos, Vitor [UNESP]; Gonçalves, Gustavo [UNESP]; Saltara, Fabio; Mello, Paulo; Dezan, Daniel; Yanagihara, Jurandir; Salviano, Leandro [UNESP] (Elsevier, 2023)
The rising importance of carbon capture, utilization and storage industry due to global warming has increased the development of new technologies. Centrifugal compressor train is an essential system required for the storage of s-CO2 into oil wells, a process known as Enhanced Oil Recovery (EOR), in which the pressurized fluid works above the critical point and close to widom-line. The optimization methodology proposed in the present work is based on One-dimensional (1D) centrifugal compressor model, capable to predict the fluid flow aspects that are not modeled through traditional and direct thermodynamic analysis. Furthermore, a Gas-like Behavior Margin (GBM) is presented to avoid high variations of thermodynamic properties on the compression process close to widom-line, avoiding transcritical phenomena that can cause damage to the equipment. A centrifugal compressor train has been proposed and an optimal configuration with four stages reduced the total power consumed by 14.09% when compared to the baseline configuration, ensuring that the fluid flow constraints as the Acceleration Margin to Condensation and Mach number at the throat is met. Moreover, a 3D CFD model for the fourth stage was built which demonstrated good agreement with 1D model and experimental data, proving the validity and clear advantages of using the methodology developed herein, as a fast and low-cost way to obtain a preliminary geometry for centrifugal compressors of train systems.
Keywords: Carbon capture, Utilization and storage; Centrifugal compressor; Enhanced oil recovery system; Gas-like behavior margin; Supercritical CO2